Anatomical factors associated with overuse sports injuries - Krivickas, L. S. (Sports Medicine, 1997)
Overuse injuries develop when repetitive stress to bone and musculotendinous structures damages tissue at a greater rate than that at which the body can repair itself. A combination of extrinsic factors, such as training errors and environmental factors, and intrinsic or anatomical factors, such as bony alignment of the extremities, flexibility deficits and ligamentous laxity, predispose athletes to develop overuse injuries. Malalignant of the lower extremity, including excess femoral anteversion, increased Q angle, lateral tibial torsion, tibia vara, genu varum or valgum, subtalar varus and excessive pronation are frequently cited as predisposing to knee extensor mechanism overuse injuries. These and other forms of malalignment have also been implicated in iliotibial band syndrome, medial tibial stress syndrome, lower extremity stress fractures and plantar fasciitis. Muscle inflexibility aggravates and predisposes to the development of a variety of overuse injuries, especially those occurring in children and adolescents, including the traction apophysitises. Flexibility deficits may be improved by an appropriate stretching programme. Unfortunately, lower extremity malalignment is less amenable to intervention. Orthotics are often prescribed to improve lower extremity alignment. However, studies have not shown that orthotics have any effect on knee alignment and, while they can alter subtalar joint alignment, the clinical benefit of this remains unclear. Awareness of anatomical factors that may predispose to overuse injuries allows the clinician to develop individual prehabilitation programmes designed to decrease the risk of overuse injury. In addition, the clinician can advise the athlete on the importance of avoiding extrinsic factors that may also predispose to overuse injury.